Navigating cultural dynamics and translation challenges to achieve equivalence while preserving meaning and context sensitively - Pande Putu Resmia Ovieta; Majid Wajdi; Muhammad Issa; Md. Kamrul Hasan; Nadia Idri; Tran Nho Huong; Dr. Mahmood Eshreteh (Journal of Education, Social & Communication Studies, 2026)
This study aims to explore the cultural dynamics and challenges involved in achieving equivalence in translation, focusing on balancing meaning and context to ensure accurate and culturally sensitive communication. The methodology includes qualitative analyses of translation cases across literary, technical, and survey contexts, employing comparative textual analysis, interviews with translators, and content analysis to examine strategies such as dynamic equivalence, localization, adaptation, and consultation with cultural informants. Analysis reveals that translators must navigate complex cultural references, idiomatic expressions, and emotional connotations while maintaining semantic, conceptual, and content equivalence. Findings highlight the importance of translators acting as cultural mediators who balance fidelity to the source text with necessary adaptations to the target culture’s norms and sensitivities. The study concludes that successful translation requires a nuanced approach that integrates linguistic accuracy with cultural competence to bridge gaps between source and target audiences effectively. Future translation efforts should emphasize collaboration with cultural experts and adopt flexible strategies to preserve both meaning and cultural context.